2015
DOI: 10.3390/jcm4050847
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Disturbances after Brain Damage: An Important and Often Undiagnosed Disorder

Abstract: Traumatic brain injury (TBI) is a common and significant public health problem all over the world. Until recently, TBI has been recognized as an uncommon cause of hypopituitarism. The studies conducted during the last 15 years revealed that TBI is a serious cause of hypopituitarism. Although the underlying pathophysiology has not yet been fully clarified, new data indicate that genetic predisposition, autoimmunity and neuroinflammatory changes may play a role in the development of hypopituitarism. Combative sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
0
20
0
6
Order By: Relevance
“…TBI is a well-known public health problem around the world, and it is associated with increased morbidity, mortality and long-term disability [65]. For instance, kickboxing is well established to be associated with a risk of TBI [31].…”
Section: Discussionmentioning
confidence: 99%
“…TBI is a well-known public health problem around the world, and it is associated with increased morbidity, mortality and long-term disability [65]. For instance, kickboxing is well established to be associated with a risk of TBI [31].…”
Section: Discussionmentioning
confidence: 99%
“…The narrow pituitary stalk is vulnerable to direct damage by mechanical compression, shearing or vascular injury, or indirectly compromised by brain swelling (Dusick et al, 2012; Reifschneider et al, 2015). Haemorrhage, necrosis and fibrosis of the pituitary stalk, anterior and posterior pituitary have been reported upon autopsy after fatal TBI (Klose and Feldt-Rasmussen, 2015; Kornblum and Fisher, 1969; Tanriverdi and Kelestimur, 2015), and amongst survivors of adult TBI, pituitary atrophy is evident by MRI up to at least 11 months post-injury (Maiya et al, 2008). Further, rodent studies have identified an inflammatory response in the hypothalamus, associated with impaired growth hormone levels, even in the absence of overt pituitary damage (Osterstock et al, 2014).…”
Section: Moving Forward: Delineating Potential Biological Mechanismsmentioning
confidence: 99%
“…The most common abnormalities are growth hormone (GH) deficiency and hypogonadism, whilst adrenocorticotrophic hormone (ACTH) and thyroidstimulating hormone (TSH) deficiencies are diagnosed less often104,105 . Almost 50% of TBI patients have anti-diuretic hormone deficiency severe enough to cause central diabetes insipidus in the acute phase following the injury, but this deficiency often resolves within 3 months105,106 .PTHP can result in a multitude of acute and chronic symptoms107 . For example, GH deficiency may result in changes in body composition and a reduction in quality of life including depression, whilst hypothyroidism may cause weight gain, low mood and blunted cognition107 .…”
mentioning
confidence: 99%
“…Almost 50% of TBI patients have anti-diuretic hormone deficiency severe enough to cause central diabetes insipidus in the acute phase following the injury, but this deficiency often resolves within 3 months105,106 .PTHP can result in a multitude of acute and chronic symptoms107 . For example, GH deficiency may result in changes in body composition and a reduction in quality of life including depression, whilst hypothyroidism may cause weight gain, low mood and blunted cognition107 . Most crucially, acute adrenal insufficiency may occur within days of TBI in some patients, with the ensuing adverse consequences of hypotension, hyponatraemia and hypoglycaemia, which require emergent treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation